THE RESULTS OF THE STUDY OF INTENTIONAL ELECTROMAGNETIC INTERFERENCE ON DISRUPTION OF THE FUNCTIONING OF UNMANNED VECHICLES - Aleksandr N. Shemonaev; Konstantin A. Epifantsev; Leonid N. Kessarinskiy; Mikhail Y. Ponchakov (Безопасность информационных технологий)
The purpose of this work is to analyze and evaluate the unmanned vehicle modules sensitivity operating in a smart-city system to the intentional electromagnetic interference. In the course of the study, sources of radio frequency interference were developed for experimental observation of reversible and irreversible failures in the functioning of individual electronic components and entire units of an unmanned vehicle. Irreversible failures (defects) that occurred due to damage to semiconductor devices in the studied vehicle engine control unit were experimentally recorded. The causes, mechanisms of damage, methods of protection and testing of resistance to electromagnetic influence of electronic components are investigated. Based on the study results, it was concluded, firstly, that modern automotive electronic units are highly sensitive (with a tendency to gradually increase) to destructive electromagnetic influences, and secondly, that the resistance of the equipment unit is determined by three factors: 1) the characteristics of the influence (frequency composition, energy, pulse duration, etc.), 2) the location of the unit, as well as the shielding and antenna properties of the vehicle's structural elements (in relation to the characteristics of the influence), 3) the resistance of the electronic components that determine the failures and malfunctions of the unit. The information presented in this article may be used to support the activities of technical committees on standardization.